Factors Affecting Parents' Decision Making in Choosing a School Private for Children during The Covid-19 Pandemic - Tukiyo Tukiyo; Bayu Indrayanto; Sri Budiyono (STAI Miftahul Ula Nganjuk, 2021)
The purpose of this study was to examine the factors that influence the way parents make decisions in choosing their favorite private school for their children during the COVID-19 pandemic. These factors are presented starting from the most influential to the smallest. In detail, the purpose of this study is to obtain answers to the questions: (1) what factors influence the way parents make decisions in choosing a favorite private school for their children, (2) are there differences in the decision-making factors of parents in choosing a school? private sector for children between before the pandemic and after the covid-19 pandemic, (3) is there a difference in the income of parents before the pandemic and after the covid-19 pandemic, and (4) how is the level of anxiety of parents in dealing with the covid-19 pandemic . This study uses a quantitative descriptive approach which is intended to describe the factors that influence parents' decision making in choosing private schools for their children during the COVID-19 pandemic. The results showed: 1. The factors that influence parents' decision making in choosing private schools for children during the covid-19 pandemic are: (1) good religious education factors in schools, (2) good academic achievement, (3) good non-academic achievement, (4) easy access to school locations, (5) schools have complete learning facilities, (6) good extra-curricular activities, (7) school safety, (8) relatively close distance from the school house, and (9) as a solution due to busy parents